Systematic Review of Teleneurology: Methodology - Rubin, Mark N.; Wellik, Kay; Channer, Dwight; Demaerschalk, Bart M. (Frontiers in Neurology, 2012)
Background: The use of two-way audio-visual (AV) technology for delivery of acute stroke is supported by a well established literature base. The use of telemedicine for general neurologic consultation has been reported across most subspecialties within the field, but a comprehensive systematic review of these reports is lacking. Purpose: To conduct a systematic review of the published literature on teleneurologic consultation beyond stroke. Data Sources: Databases Ovid MEDLINE, EMBASE, PsychINFO, CINAHL and Cochrane were searched with keywords, “teleneurology” and numerous synonyms and cross-referenced with neurology subspecialties. The search yielded 6,615 potentially eligible hits, which were independently reviewed by two investigators. Ultimately 375 unique studies met eligibility criteria and were included in the review. Study Selection: Studies were included if the title or abstract expressed use of two-way AV communication for a clinical neurologic indication other than stroke. Data Extraction: Each article was classified using a novel scoring rubric to assess the level of functionality, application, technology, and evaluative stage (FATE). Data Analysis: Articles were hierarchized within a subspecialty category. Overall subspecialty scores were assigned based on aggregate of scores across papers in each category. Conclusions: Use of telemedicine for general and most subspecialty neurologic consultation, beyond stroke, appears very promising but the clinical science is nascent.